Focused Cardiac Ultrasound Examination as a Tool for Diagnosis of Infective Endocarditis and Myocarditis in Dogs and Cats - Olga Szaluś-Jordanow (MDPI AG, 2021)
Symptoms of infective endocarditis (IE) and myocarditis are usually nonspecific and include fever, apathy, and loss of appetite. This condition can lead to severe heart failure with ascites or/and fluid in the thoracic cavity or/and in the pericardial sac. We describe infective endocarditis and myocarditis in 3 dogs and 4 cats. In all animals, the initial diagnosis was performed on the basis of a focused cardiac ultrasound examination performed by a general practitioner after a training in this technique. The initial findings were confirmed by a board-certified specialist in veterinary cardiology. Post mortem positive microbiological results from valves were obtained in 4 of 7 patients. Methicillin-resistant Staphylococcus aureus was confirmed in 2 cases and Staphylococcus epidermidis was confirmed in 2 cases, one of which included Enterococcus sp. coinfection. Histopathological examination confirmed initial diagnosis in 5 of 7 animals. In the remaining 2 patients, the time elapsed from the onset of clinical symptoms to death was about 1 month and no active inflammation but massive fibrosis was found microscopically. This is, to our best knowledge, the first report of IE and myocarditis diagnosed in small animals using focused cardiac ultrasound examination. Therefore, we conclude that common usage of this technique by trained general veterinarians may increase the rate of diagnosed patients with these conditions.